Exploitation of cryptocurrencies as a tool for tax evasion: technological and regulatory issues - Vaivade, Anna (Riga Graduate School of Law, 2020)
Tax evasion is a crime that harms the national economies, society and indirectly affects all the residents of each state. Now that after a long time of international efforts the traditional tax evasion tools have eventually been put under a reasonable control, a new technology has emerged able to facilitate efficient tax evasion. The main objectives of this research are to identify the regulatory challenges of the non-precedent technology, to analyse the applicability of the current EU legislation aimed at tax evasion prevention to the exploitation of cryptocurrencies, and to assess the recommendations of academics and international organizations for a possible future regulation. This research resulted establishing that tax evasion through cryptocurrencies is easy to perform at efficient level for the consumers while difficult to discover for the authorities. Due to the novel way of operation of the distributed ledger technology on which cryptocurrencies are based, cryptocurrencies cannot be placed under the existing regulation, instead an innovative approach is required. Each of the analysed proposition for the future regulation can only partly solve some of the challenges presented by the cryptocurrencies as a tool for tax evasion therefore a complex and globally consented approach needs to be developed.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Taxation; Cryptocurrencies